An evaluation of the effectiveness of oral health workers training done by community dentistry interns in San Juan, Batangas (AY 2011-2012) - Aguilar, Camille A.
INTRODUCTION. An Oral Health Workers (OHW) training was conducted for selected Barangay Health Workers (BHW) from the 4 clusters of San Juan, Batangas, This was part of the overall objective of improving access to oral health care for the community. The BHWs attended 3 half-day sessions of the oral health training. To pass this training, a written examination and actual tooth brushing activity on an articulator was made. This study evaluates the effectiveness of the OHW training a year after it was conducted using the Kirkpatrick model. It also aims to determine areas of the training that may need further improvement.